Ambedkar, Indian Constitution and Making of Indian Republic - Pandey, Neelam (New Delhi 178566, 2018)
When India was drawing up her Constitution, there weren$1 (Bt too many examples for her to refer to. Not many Constitutions at that point had stood the test of time. The British Constitution was not codified and was based on convention. While its principles could be adopted, it offered little drafting precedent. The Swiss with their then-three-hundred-year-old Constitution were there. There were the British North America Acts which formed the Constitution for Canada and the Commonwealth of Australia Constitution Act, 1900 but they retained constitutional links with the United Kingdom. Two young Constitutions were useful though: one was the Constitution of the Irish Free State, 1922 and the other was the Constitution of the Weimar Republic, 1919. The other key inspiration was of course, the US Constitution. The drafting committee of the Constituent Assembly studied these constitutions in detail. The committee was chaired by an able statesmen and draftsman in the form of Dr BR Ambedkar. This book is an effort to understand Dr. Ambedkar$1 (Bs contribution and a wide-ranging, analytical reflection on the major themes and debates that surround India$1 (Bs Constitution. It is a valuable book for all those study and belongs to constitution, judiciary, law and politics.s
Keywords: Ambedkar and Indian Constitution -- The Basic Structure of the Indian Constitution